1001 BEST HEALTH HINTS & TIPS - McPhee, Margaret; Kent, Samantha (Sydney, N.S.W. Reader's Digest, 2013)
Plagued by colds? Can't get rid of backache? Find dry eyes a real problem? Whether you have a particular ailment you want to overcome quickly or need help managing a chronic condition, here are dozens of remedies that really help, all doctor-approved. Many of them are based on gentle natural treatments that avoid the need for heavy-handed medical intervention. With 1,001 tips included, there's certain to be plenty here to keep you and your loved ones as well and as happy as possible. All are designed to fit easily into your everyday routine and all will cumulatively build good health.
Includes index
Keywords: Health